Career Development, Employee Competence, Work Culture and Communication on Employee Performance at Sukoharjo Pratama KPP - Triyanto Triyanto; Kartika Hendra TS; Sarsono Sarsono (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to test and analyze the influence of career development, employee competency, work culture, and communication on the performance of KPP Pratama Sukoharjo employees both partially and simultaneously. This research method uses a quantitative research design. The population is all employees working at KPP Pratama Sukoharjo, totaling 109 people. The sampling technique used in this study is the Census technique with a sample size of 109 respondents. Data collection uses a questionnaire. The data analysis technique used is statistical analysis, namely multiple linear regression tests, F tests, t tests, and coefficients of determination. The results of the study show that career development has a significant effect on the performance of Sukoharjo Pratama Tax Office employees. Employee competence has a significant effect on the performance of Sukoharjo Pratama Tax Office employees. Work culture has a significant effect on the performance of Sukoharjo Pratama Tax Office employees. Communication has a significant effect on the performance of Sukoharjo Pratama Tax Office employees. Career development, employee competence, work culture, and communication have a simultaneous and significant effect on the performance of Sukoharjo Pratama Tax Office employees. The determination or contribution of the variables Career development, employee competence, work culture, and communication have a simultaneous and significant effect on the performance of Sukoharjo Pratama Tax Office employees by 78.2%, while 21.8% is influenced by other variables. Keywords: employee performance, career development, employee competency, work culture and communication